Advances in library administration and organization. Vol. 22 - Nyce, James M.; Williams, Delmus Eugene; Garten, Edward D. (Advances in library administration and organization,, 2005)
This volume of Advances in Library Administration and Organization offers papers of interest to practitioners and researchers in the library community throughout the world. All of the papers in one way or another address the tension between what researchers can deliver, what they define as reputable knowledge, and what library practitioners need to know to get the job done. While these papers differ from each other by problem, scale, methodology and theory, one question What can science tell us about practice? unites them all. These papers include a discussion of the principles that underlie collection development, two papers that critically examine the relation between distance learning and on site library service and two more papers that use the notion of sense making to look at what the terms leadership and public space mean when we talk about libraries.The last three papers address a series of pragmatic issues anyone who works within a library can identify with, namely, what does it mean to market a library, how can we define value in relation to what goes on in a library and create value for our communities, and, finally, What constitutes and impedes 'success for library professionals? , especially if those who are minority women. These papers, taken together, raise the issues of how well we understand, researchers and practitioners alike, the institutions we study, manage and work within. What we in the profession often regard as common sense and good practice may not really be either. In short, these papers point to a number of issues, ones we often do not even acknowledge, that researchers need to help practitioners address if science is to make a difference in how librarians understand and manage the institutions they work within.